Prevalence of key resistance alleles associated with DMI and SDHI fungicide resistance in European Zymoseptoria tritici populations in 2022 - S. Kildea; T. Heick; F. Hutton; C. Bataille; L. Aldén; J. Kaneps; A. Mäe; S. Weigand; J. Zajc; A. S. Walker; P. Hellin (Journal of Plant Diseases and Protection, 2025)

Characterization of sites of scientific interest for ESA's PROSPECT instrument - S.J. Boazman; D. Heather; M. Hutton; M. Schwinning; A. Frigeri; N. Schmitz; S. Besse; M. Formisano; C. De Sanctis; C. Gscheidle; C. Orgel; P. Reiss; et al. (Icarus, 2024)

The potential effects of climate change on subsistence farmers’ wellbeing in tropical (sub)montane homegardens. A case study on Mount Kilimanjaro - Martin Watts; Craig Hutton; Abel Paul; Natalie Suckall; Kelvin S.-H. Peh (Journal of Rural Studies, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Exploring the pathology of liver, kidney, muscle, and stomach of fledgling seabirds associated with plastic ingestion - Peter S. Puskic; Ron Slocombe; Richard Ploeg; Lauren Roman; Mary-Anne Lea; Ian Hutton; Andrew R. Bridle (Journal of Hazardous Materials, 2024)

Objective and Subjective Measurements of Freshmen and Sophomore’s Fruit and Vegetable Intake - T. Ibiyemi; W. Najam; A. Sosa; S. Makerecha; T. Hutton; S. Bryant; W. Oldewage-Theron (Journal of the Academy of Nutrition and Dietetics, 2023)

Natural and synthetic microfibers alter growth and behavior in early life stages of estuarine organisms - S. Siddiqui; S. J. Hutton; J. M. Dickens; E. I. Pedersen; S. L. Harper; S. M. Brander (Frontiers in Marine Science, 2023)
Increasing shares of microfibers are being detected in environmental samples and a closer look to identify the risk associated with them using ecologically relevant endpoints, especially at sensitive early life stages, is needed. To assess exposure hazards, we used rope samples representative of fiber types ubiquitous in coastal systems, where microfibers are often the most common debris type found in the water column. To compare responses to natural vs. synthetic microfibers, we used rinsed “natural” cotton, polyester, and polypropylene microfibers (80-150 µm length, 8-20 µm width) created from the rope. Larval and juvenile estuarine indicator species Inland Silverside (Menidia beryllina) and mysid shrimp (Americamysis bahia) , respectively, were exposed to these three microfiber types at three concentrations (3, 10, 30 particles/ml) along a 5-25 PSU salinity gradient to mimic estuarine conditions. Behavioral responses, growth, and ingestion were measured. The cotton microfibers were not detected in the digestive tracts of Silversides, however, both the polyester and polypropylene microfibers were detected in the Silversides’ stomach and gut lining. None of the fiber types were detected in mysid shrimps. Mysids exposed to cotton microfibers had fewer behavioral effects compared to Silversides, who responded more to cotton. Cotton exerted no effect on growth in Silversides but did cause reduced growth in the mysids at the two lower salinities. In contrast, polyester and polypropylene were identified to have a significant dose dependent effect on mysid and Silverside behavior as well as growth was affected in at least one of the three salinities at concentrations as low as 3 particles/ml. Cotton impacted both the organism’s behavior more at higher salinities, whereas polyester and polypropylene had more impacts at lower salinities. This raises concerns for microfiber impacts on estuarine ecosystems and the need for policies to limit microfiber production and outfall into the aquatic environment.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Data-Driven, Multi-Model Workflow Suggests Strong Influence from Hurricanes on the Generation of Turbidity Currents in the Gulf of Mexico - Courtney Harris; Jaia Syvitski; H.G. Arango; E.H. Meiburg; Sagy Cohen; C.J. Jenkins; Justin Birchler; E.W.H. Hutton; T.A. Kniskern; S. Radhakrishnan; Guillermo Auad (Journal of Marine Science and Engineering, 2020)
Turbidity currents deliver sediment rapidly from the continental shelf to the slope and beyond; and can be triggered by processes such as shelf resuspension during oceanic storms; mass failure of slope deposits due to sediment- and wave-pressure loadings; and localized events that grow into sustained currents via self-amplifying ignition. Because these operate over multiple spatial and temporal scales, ranging from the eddy-scale to continental-scale; coupled numerical models that represent the full transport pathway have proved elusive though individual models have been developed to describe each of these processes. Toward a more holistic tool, a numerical workflow was developed to address pathways for sediment routing from terrestrial and coastal sources, across the continental shelf and ultimately down continental slope canyons of the northern Gulf of Mexico, where offshore infrastructure is susceptible to damage by turbidity currents. Workflow components included: (1) a calibrated simulator for fluvial discharge (Water Balance Model - Sediment; WBMsed); (2) domain grids for seabed sediment textures (dbSEABED); bathymetry, and channelization; (3) a simulator for ocean dynamics and resuspension (the Regional Ocean Modeling System; ROMS); (4) A simulator (HurriSlip) of seafloor failure and flow ignition; and (5) A Reynolds-averaged Navier–Stokes (RANS) turbidity current model (TURBINS). Model simulations explored physical oceanic conditions that might generate turbidity currents, and allowed the workflow to be tested for a year that included two hurricanes. Results showed that extreme storms were especially effective at delivering sediment from coastal source areas to the deep sea, at timescales that ranged from individual wave events (~hours), to the settling lag of fine sediment (~days).

Differences in functional brain network connectivity during stories presented in audio, illustrated, and animated format in preschool-age children - John S. Hutton; Jonathan Dudley; Tzipi Horowitz-Kraus; Tom DeWitt; Scott K. Holland (Brain Imaging and Behavior, 2020)

Impact of various lipophilic substituents on ruthenium(II), rhodium(III) and iridium(III) salicylaldimine-based complexes: synthesis, in vitro cytotoxicity studies and DNA interactions - Irwin Cassells; Tameryn Stringer; Alan T. Hutton; Sharon Prince; Gregory S. Smith (JBIC Journal of Biological Inorganic Chemistry, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Detection of infectious bronchitis virus 793B, avian metapneumovirus, Mycoplasma gallisepticum and Mycoplasma synoviae in poultry in Ethiopia - S. Hutton; J. Bettridge; R. Christley; T. Habte; K. Ganapathy (Tropical Animal Health and Production, 2017)

Estrogen, progesterone, and HER2/neu receptor discordance between primary and metastatic breast tumours—a review - C. Yeung; J. Hilton; M. Clemons; S. Mazzarello; B. Hutton; F. Haggar; C. L. Addison; I. Kuchuk; X. Zhu; K. Gelmon; A. Arnaout (Cancer and Metastasis Reviews, 2016)

The quandary of quota management in the T orres S trait rock lobster fishery - I. van Putten; R. Deng; D. Dennis; T. Hutton; S. Pascoe; E. Plagányi; T. Skewes (Fisheries Management and Ecology, 2013)
Islanders, commercial non‐indigenous fishers and P apua N ew G uinea fishers share the tropical rock lobster fishery, P anulirus ornatus ( F abricius) in T orres S trait. As the fishery is in the process of moving from input to output controls, a pre‐implementation understanding of indigenous fishers' perceptions of the potential impact of different quota management systems is gained. This study, based on workshops and interviews, considers the impact of competitive quota, community quota and a hybrid system with individually tradeable quota ( ITQ ), and broadens the current biological focus of fisheries management through consideration of economic, social and cultural aspects. The perceived quota system impact on indigenous lobster fishers largely mirrors the experience internationally, with unlimited access and self‐determination considered most important. The heterogeneity of the indigenous sector increases the management complexity for this fishery, but needs to be taken into consideration if unexpected consequences of the chosen quota management system are to be avoided.

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

Error awareness and antisaccade performance - A. J. G. Taylor; S. B. Hutton (Experimental Brain Research, 2011)

Outbreak of angular leaf spot, caused by Xanthomonas fragariae, in a Queensland strawberry germplasm collection - Anthony J. Young; Thomas S. Marney; Mark Herrington; Don Hutton; Apollo O. Gomez; Adam Villiers; Paul R. Campbell; Andrew D. W. Geering (Australasian Plant Pathology, 2011)

Quantitative differences in intervertebral disc–matrix composition with age-related degeneration - Hideki Murakami; Tim S. Yoon; Emad S. Attallah-Wasif; Chaiwat Kraiwattanapong; Ichiro Kikkawa; William C. Hutton (Medical & Biological Engineering & Computing, 2010)

How sympatric is speciation in the Howea palms of Lord Howe Island? - WIESŁAW BABIK; ROGER K. BUTLIN; WILLIAM J. BAKER; ALEXANDER S. T. PAPADOPULOS; MATTHIEU BOULESTEIX; MARIE‐CHARLOTTE ANSTETT; CHRISTIAN LEXER; IAN HUTTON; VINCENT SAVOLAINEN (Molecular Ecology, 2009)
The two species of the palm genus Howea (Arecaceae) from Lord Howe Island, a minute volcanic island in the Tasman Sea, are now regarded as one of the most compelling examples of sympatric speciation, although this view is still disputed by some authors. Population genetic and ecological data are necessary to provide a more coherent and comprehensive understanding of this emerging model system. Here, we analyse data on abundance, juvenile recruitment, pollination mode and genetic variation and structure in both species. We find that Howea forsteriana is less abundant than Howea belmoreana . The genetic data based on amplified fragment length polymorphisms markers indicate similar levels of variation in the two species, despite the estimated census population size of H. belmoreana being three times larger than that of H. forsteriana . Genetic structure within species is low although some weak isolation by distance is detectable. Gene flow between species appears to be extremely limited and restricted to early‐generation hybrids – only three admixed individuals, classified as F2s or first generation backcrosses to a parental species, were found among sampled palms. We conclude that speciation in Howea was indeed sympatric, although under certain strict definitions it may be called parapatric.

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Low frequency rTMS over posterior parietal cortex impairs smooth pursuit eye tracking - Samuel B. Hutton; Brendan S. Weekes (Experimental Brain Research, 2007)

Non-cholinergic modulation of antisaccade performance: a modafinil-nicotine comparison - N. Rycroft; S. B. Hutton; O. Clowry; C. Groomsbridge; A. Sierakowski; J. M. Rusted (Psychopharmacology, 2007)

Field resistance of annual pasture legumes to the root lesion nematode, Pratylenchus neglectus - R. A. Ballard; R. E. Hutton; S. P. Taylor; A. C. McKay; J. H. Howie (Australasian Plant Pathology, 2006)

The effects of dividing attention on smooth pursuit eye tracking - S. B. Hutton; D. Tegally (Experimental Brain Research, 2005)

Plant hosts of the phytoplasmas and rickettsia-like-organisms associated with strawberry lethal yellows and green petal diseases - Claire Streten; Mark E. Herrington; Don G. Hutton; Denis M. Persley; Geoff K. Waite; Karen S. Gibb (Australasian Plant Pathology, 2005)

Rickettsia-like-organisms and phytoplasmas associated with diseases in Australian strawberries - Claire Streten; Geoff K. Waite; Mark E. Herrington; Don G. Hutton; Denis M. Persley; Karen S. Gibb (Australasian Plant Pathology, 2005)

Turbulence Statistics Measurements in a Northern Hardwood Forest - M. G. Villani; H. P. Schmid; H.-B. Su; J. L. Hutton; C. S. Vogel (Boundary-Layer Meteorology, 2003)

Short and long term effects of antipsychotic medication on smooth pursuit eye tracking in schizophrenia - S. Hutton; T. Crawford; H. Gibbins; I. Cuthbert; T. Barnes; C. Kennard; E. Joyce (Psychopharmacology, 2001)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)

Ionic imbalance as a source of toxicity in an estuarine effluent - W. S. Douglas; S. S. Grasso; D. G. Hutton; K. R. Schroeder (Archives of Environmental Contamination and Toxicology, 1996)

Accumulation and renal effects of lead in urban populations of feral pigeons,Columba livia - M. S. Johnson; H. Pluck; M. Hutton; G. Moore (Archives of Environmental Contamination and Toxicology, 1982)